Alcohol and social connectedness for new residential university students: implications for alcohol harm reduction. Issue 2 (7th February 2020) - Brown, Rachel; Murphy, Simon
ABSTRACT: Starting university is a significant life-event, commonly involving detachment from existing social networks and emotional stresses that increase risk of drop-out. The developmental need to form new peer relationships is prominent during this period and is correlated with successful adaptation. This study investigated the role of alcohol in the process of transition and peer group development for new students. Thematic analysis of semi-structured interviews is presented, conducted within a broader instrumental case study of campus approaches to alcohol policy and management. Twenty-three first-year students participated in interviews lasting between 45–60 minutes. Verbatim transcription was followed by within- and cross-case analysis. Drawing on social connectedness theory, we illustrate how pre-arrival concern over new peer relationships was subsequently reduced by drinking together. This reinforced participant perceptions of alcohol as beneficial for hastening development of social connections, in turn reducing anxiety and supporting successful transition. For non-/low-drinkers in the study, social connectedness without alcohol use was reported as more challenging. Alcohol was perceived as a readily-available, effective tool for hastening social connectedness, increasing student resistance to alcohol education messages provided at the start of term. Implications for addressing alcohol-related harms in students are discussed.